Output-Feedback Shared-Control for Fully Actuated Linear Mechanical Systems - Jiang,J; Astolfi,A (IEEE, 2014)
This paper presents an output feedback shared-control algorithm for fully-actuated, linear, mechanical systems. The feasible configurations of the system are described by a group of linear inequalities which characterize a convex admissible set. The properties of the shared-control algorithm are established with a Lyapunov-like analysis. Simple numerical examples demonstrate the effectiveness of the strategy.